Waiting For The Revolution To End Syrian displacement, time and subjectivity - Al-Khalili, Charlotte (UCL Press, 2023)
Waiting for the Revolution to End explores the Syrian revolution through the experiences of citizens in exile. Based on more than three years of embedded fieldwork with Syrians displaced in the border city of Gaziantep (southern Turkey), the book places the Syrian revolution and its tragic aftermath under ethnographic scrutiny. It charts the evolution from peaceful uprising (2011) to armed confrontation (2012), descent into fully fledged conflict (2013) and finally to proxy war (2015), to propose an understanding of revolution beyond success and failure. While the Assad regime remains in place, the Syrian revolution (al-thawra) still holds a transformational power that can be located on intimate and world-making scales. Charlotte Al-Khalili traces the unintended consequences of revolution and its unexpected consequences to reveal the reshaping of Syrian life-worlds and exiles' evolving theorizations, experiences and imaginations of al-thawra. She describes the in-between spatio-temporal realm inhabited by Syrians displaced to Turkey as they await the revolution's outcomes, and maps the revolution's multidimensional and multi-scalar effects on their everyday life. By following the chronology of events inside Syria and Syrians' geography of displacement, the book makes the relation between revolution and displacement its centerpiece, both as an ethnographic object and an analytical device. Praise for Waiting for the Revolution to End 'Waiting for the Revolution to End is essential reading for scholars and students wanting to understand the temporal and affective orientations at play in the aftermath of the Syrian revolution. Al-Khalili presents a lucid ethnography of revolutionary hopes, defeat, and displacement hereby offering a sustained theoretical engagement with the social, political and religious forces that undergird Syrian existence.' Andreas Bandak, University of Copenhagen 'Although so much has been said about the Syrian revolution, surprisingly little has been written about what it did to the selves, hopes, and lives of those who joined it but were defeated. Waiting for the Revolution to End is a very important and urgently needed contribution that tells the story of the revolution as it is understood by ordinary Syrians who turned into revolutionaries by participating in the uprising from its beginnings in 2011 and 2012, when the possibility of a non-violent overcoming of a violent regime still appeared within reach. Writing through the experience of living among displaced Syrians in Gaziantep, Al-Khalili tells us something that political analyses from above so often miss: the transformational power of participation in the revolution, and the cosmogonic change it effected in the minds and lives of people while they were tragically defeated. Speaking of defeat rather than failure of Syrian revolutionaries, Waiting for the Revolution to End *weaves a rich, emphatic, convincing, tragic yet also hopeful story of the possibility of dignity.' Samuli Schielke, Leibniz-Zentrum Moderner Orient 'Charlotte Al-Khalili's stunning and moving ethnography is a landmark in the study of revolution, social change and mobility. Through an extraordinary portrayal of the lives, hopes and fears of Syria's exiled revolutionaries in their "capital", Al-Khalili transforms understandings of how migration shapes revolutionary subjectivity, how grassroots revolutionary activists theorize revolutionary outcomes, and how revolutionaries reorganize families and networks to keep ideals of social transformation alive.' Alice Wilson, University of Sussex